Silent creed [large type] - Kava, Alex (Kava, Alex. Ryder Creed novels, 2015)
There has been a major landslide in North Carolina's Haywood County. At the disaster site, the continual downpour makes the search for survivors dangerous. Among the missing are scientists working on a classified project at the local branch of the Defense Advanced Research Projects Agency. After one of the bodies recovered by Creed's team turns out to be a murder victim, FBI agent Maggie O'Dell, joins in the homicide investigation. The suspense rises when Creed gets trapped in a mudslide, though he has reason to hope Bolo has escaped to bring help.